Fetal Superior Vena Cava Blood Flow and Its Fraction of Cardiac Output: A Longitudinal Ultrasound Study in the Second Half of Pregnancy - Stefopoulou, Maria; Johnson, Jonas; Herling, Lotta; Lindgren, Peter; Kiserud, Torvid; Acharya, Ganesh (Frontiers in Pediatrics, 2021)
Introduction: In the fetus, a large proportion of the superior vena cava blood flow (QSVC) comes from the brain. To provide the possibility of using this blood flow as a representation of fetal brain circulation, we aimed to determine the fetal QSVC and its fraction of cardiac output during the second half of physiological pregnancies. Materials and Methods: This was a prospective longitudinal study specifically designed for studying fetal hemodynamic development. Healthy women with singleton low-risk pregnancies were included. Ultrasonography was performed at 4-weekly intervals from 20+0 gestational weeks to term. Doppler velocity recordings of the superior vena cava (SVC) and cardiac ventricular outflow tracts were used to obtain the time-averaged maximum velocities (TAMxV). Vessel diameters were measured to calculate their cross-sectional areas (CSA): π(diameter/2)2. Blood flow (Q) was computed as: h*TAMxV*CSA, h being the spatial blood velocity profile, to obtain QSVC and cardiac outputs. The sum of left and right ventricular cardiac outputs constituted the combined cardiac output (CCO). Ultrasound biometry based estimated fetal weight and estimated brain weight were used to normalize the flow. QSVC was also expressed as the fraction (%) of CCO. Gestational age specific percentiles were established for each blood flow parameter using multilevel modeling. Results: Totally, 134 of the 142 included women were eligible for the study with 576 sets of observations. The SVC mean diameter (19–52 mm), mean TAMxV (8.83–16.14 cm/s), and QSVC (15.4–192.0 ml/min) increased significantly during the second half of pregnancy (p<0.001) while the mean QSVC normalized by estimated fetal weight (49 ml/min/kg) and by brain weight (50 ml/min/100g) were relatively stable. Similarly, the mean CCO increased (156–1776 ml/min; p<0.001) while the normalized CCO (50913 ml/min/kg) and QSVC as a fraction of CCO (100.92%) did not change significantly with gestational age. Conclusion: We provide reference values for fetal QSVC which increases significantly with gestation, and constitutes roughly 10% of the fetal CCO at any time during the second half of pregnancy.